A case of massive fetal cardiac rhabdomyoma: ultrasound features and management. (31st December 2023) - Montaguti, Elisa; Gesuete, Valentina; Perolo, Antonella; Balducci, Anna; Fiorentini, Marta; Donti, Andrea; Pilu, Gianluigi
Abstract: We report the case of a massive fetal cardiac rhabdomyoma recently occurred at our clinic. A woman at 23 weeks of gestational age was referred to our center for a fetal cardiac echogenic mass of 26 mm detected at the second-trimester screening ultrasound. During pregnancy, though, the mass progressively increased its dimensions until reaching 48 mm in diameter at 37 weeks of gestation. Fetal echoencephalography and brain magnetic resonance did not show any further fetal anomalies, but molecular genetic testing at amniocentesis revealed a heterozygotic missense variant of gene TSC2 associated with Tuberous Sclerosis. The mass was therefore most likely preferable to a single large rhabdomyoma of gradually increasing dimensions. The baby was delivered at term with a cesarean section. Because of the rhabdomyoma remarkable size and newborn ECG electrical alterations, postnatal therapies with Flecainide and Everolimus were started. Everolimus treatment led to a significant and progressive reduction in the cardiac mass volume. This case, therefore, shows the efficacy of what seems to be a promising treatment in pediatric patients with large rhabdomyomas. Learning points: Rhabdomyomas may present with different features: most often they appear as multiple masses along the interventricular sept, but they may also appear as a single large thoracic mass. When a rhabdomyoma is suspected, genetic counseling is recommended. Both before and after birth, a multidisciplinary approach is useful to choose the appropriate therapy for the newborn. mTOR inhibitors therapies look like promising therapeutic approaches to stimulate the involution of rhabdomyomas.